Increased Learning Outcomes in Effective Learning Models Application According to the Plomp - Hidayat, Irwin; Naziha, Nur; Purnama, Atmaranie Dewi (Universitas Islam Ahmad Dahlan (UIAD), 2022)
The study deals with a background of problems that still lack the ability of learners to receive learning because of invalid materials, impractical methods and ineffective material delivery. One way to overcome the problem is to change the learning model so that learners can receive learning well. The study aims to solve the problem of learners' learning methods and to improve the learning performance of learners with plomp study models. The study is done with a design design of learning, a plomp study model consisting of a pleminary research, phototyping phase, and enforcing phase with a valid, practical, and effective teaching device. This study is based on the development of the plomp study model with a sample of thirty students at the country's in 12 sinjai high school, which is an improvement in the study of islamic trainees, especially those being tested with islamic test analyses.